Design of microstrip branch transmission line for open-circuit stub / Mohamad Shahbudin Mohamad Ali - Mohamad Ali, Mohamad Shahbudin (2001)
The aim of this project to design of a 3 dB single section branch-line coupler. The branch-line coupler is designed to operate at 2 GHz. The initial circuit was designed and simulated on HP Eesof Libra. This project report is organized into five chapters. Chapter 1 presents an overview of this final project. The types of branch-line coupler are explained in Chapter 2. Chapter 3 presents the design simulation and hardware implementation technique used in this final project. The measurement results are presented in Chapter 4. The discussion and conclusion of this final project will be presented in Chapter 5.